Female êthos in the inaugural addresses of South America’s first women presidents: Michelle Bachelet, Cristina Fernández de Kirchner and Dilma Rousseff (Anclajes, 2014)
We have analysed the construction of a female êthos in the inaugural speeches of Michelle Bachelet (2006), Cristina Fernández de Kirchner (2007) and Dilma Rousseff (2011). On the one hand, we have noticed that all three speakers appeal to the fact that they are women to legitimate their political leadership but, on the other hand, they show different degrees of confrontation, do not articulate êthos with logos and pathos in the same way, and do not appeal to the same stereotypes about women, making it difficult to speak of a single female êthos.
Keywords: female êthos; inaugural address; Michelle Bachelet; Cristina Fernández de Kirchner; Dilma Rousseff